1990
DOI: 10.2337/diab.39.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene—Related Peptide and Induction of Hyperglycemia in Conscious Rats In Vivo

Abstract: The effect of calcitonin gene-related peptide (CGRP) on glucose metabolism was investigated in conscious and unrestrained rats in vivo. Intravenous injection of rat CGRP (5.67 and 0.567 nmol/kg) caused a significant, dose-dependent increase in plasma glucose concentration and a simultaneous dose-dependent increase in plasma insulin level. In contrast, plasma glucagon level was not changed. On the other hand, intravenous infusion of CGRP (46.6 pmol.kg-1.min-1) decreased tolerance to intragastric administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Indeed, a l-year-old Cap-Des rat has a concentration of CGRP in its blood equal to that characteristic of a five-week-old rat (38). CGRP is known to induce insulin resistance in muscle in rats, both in vivo and in vitro (5,23,35,39). Moreover, the concentration of CGRP in blood of old rats, about 70 pM (37,38), might even be capable of antagonizing the action of insulin, since a maximum inhibition of insulin-stimulated glucose uptake by soleus muscle in vitro is achieved at a peptide concentration of 10 pM (23).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a l-year-old Cap-Des rat has a concentration of CGRP in its blood equal to that characteristic of a five-week-old rat (38). CGRP is known to induce insulin resistance in muscle in rats, both in vivo and in vitro (5,23,35,39). Moreover, the concentration of CGRP in blood of old rats, about 70 pM (37,38), might even be capable of antagonizing the action of insulin, since a maximum inhibition of insulin-stimulated glucose uptake by soleus muscle in vitro is achieved at a peptide concentration of 10 pM (23).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, CGRP-induced vasodilation and nociceptive effects are impaired after the onset of diabetes, which can explain the reduced prevalence of migraine attacks ( 62 ). Certainly, CGRP exerts a hyperglycaemic effect ( 183 ), but the evidence has shown that diabetic individuals presented lower CGRP levels (see Table 1 ). Since hypoglycemia is responsible for triggering and exacerbating migraine ( 59 ) (probably due to CGRP-induced hyperinsulinemia), this could suggest an inverse relationship between migraine and DM.…”
Section: Association Between Migraine and Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Conversely, Sun et al (2010) reported increased plasma glucagon in 24-h fasted rats by IP CGRP, thus suggesting that CGRP induce opposite effects in different rodent models. In a rat model, Pettersson and Ahrén (1988) found increased basal glucagon but inhibited glucose-stimulated glucagon upon IV infusion of CGRP, whereas Yamaguchi et al (1990), using a CGRP IV treatment in conscious male rats, reported no changes in glucagon. In addition, an in vitro study, using dog intestine perfused with CGRP, showed no significant changes in glucagon secretion (Hermansen and Ahrén 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Pettersson and Ahrén (1988) reported increased basal insulin secretion and inhibition of glucose-stimulated insulin secretion after IV infusion of CGRP in rats. Conversely, Yamaguchi et al (1990) described that IV-administered CGRP dose-dependently increased plasma insulin in rats. In another study, patients fasted overnight and then IV infused with rat CGRP had normal insulin (Kraenzlin et al 1985).…”
Section: Discussionmentioning
confidence: 99%